An efficient methodological approach in the didatic of automation applied to integrated manufacturing - Botura Jr., Galdenoro [UNESP]; De Lemos, Marilza A. [UNESP]; Marques, Marcio A. [UNESP] (My University, 2007)
This work presents challenges and solutions for the teaching and learning of automation applied to integrated manufacturing by means of a methodological approach based on techniques, tools and industrial equipment directly applicable in the industry. The approach was implemented in a control and automation engineering course divided into expositive and laboratory classes. Since the success of the approach is mainly from the practical activities, the article focus more on activities developed in laboratory than theorical classes. Copyright © 2007 IFAC.
Keywords: Education; Factory automation; Flexible manufacturing system; Programmable logic controllers; Robotic; Control and automation; Industrial equipment; Integrated manufacturing; Laboratory class; Methodological approach; Programmable logic; Teaching and learning; Controllers; Cost effectiveness; Product development; Teaching; Flexible manufacturing systems